LITHUANIANS’ ATTITUDES TOWARDS FAMILY RIGHTS OF THE SAME GENDER COUPLES - Navaitis, Gediminas; Gaidys, Vladas (Sociologija. Mintis ir veiksmas, 2016)
A discussion about family rights of the same sex couples plays an important role in a discourse of the family’s institution future. For this reason it is important to know the public opinion (attitudes) towards these rights (right to register a family, right to adopt and educate a child for homosexuals). In October 2014, a representative survey was carried out and 1005 adult respondents were interviewed. According to this survey, majority of the population (86,3%) is against the possibility to register a marriage for homosexuals, and even more (94,8%) is against the possibility to adopt a child. More tolerant towards the rights of homosexuals is the younger generation, people having university education, living in big towns (especially in Vilnius).
Keywords: homosexualism; family rights of the same gender couples; a representative survey